Self-control and resilience on academic performance among undergraduate students in Malaysia - Eyone, Neo; Chan, Weng Hoe; Thayanhithy, Veeraramany (2022)
The present study investigated the relationship between self-control, resilience, and academic performance among undergraduate students in Malaysia, researching how self-control and resilience influence students’ academic results and how self-control affect resilience. Only a few studies the impact of self-control on academic performance, and previous studies on resilience used adolescents as their target sample rather than university undergraduates and were less in Malaysia context. In this study, researchers hypothesised that there is meaningful relationship between self-control, resilience, and academic performance among undergraduate students. Participants (N=94) who are students studying in Malaysia’s university and are between 20 to 24 years old were recruited by using cross-sectional study design and snowball sampling method for them to provide response for a survey through Qualtrics. Brief Self-Control Scale (BSCS) and Academic Resilience Scale-30 (ARS-30) are two instruments that used to measure the students’ trait self-control and degree of resilience respectively, while academic performance is detected through CGPA. Results showed that self-control and academic performance were related (r = .232, p < .05), self-control and resilience have a significant relationship (r = .429, p < .01), while resilience has no significant relationship with academic performance (r = .064, p > .05). This study can be used as a starting point to research and produce findings regarding the influences of self-control and resilience on academic performance in Malaysia context. Academics and psychological experts can use this research as a resource and a chance to get motivated to investigate other causal factors that could improve academic performance.